Efficiency of activated natural zeolite-based magnetic composite (ANZ-Fe3O4) as a novel adsorbent for removal of Cr(VI) from wastewater - Yantus A.B. Neolaka; Yosep Lawa; Johnson Naat; Arsel A.P. Riwu; Anggelina Walo Mango; Handoko Darmokoesoemo; Bernadeta Ayu Widyaningrum; Munawar Iqbal; Heri Septya Kusuma (Journal of Materials Research and Technology, 2022)
The increase of Cr(VI) ion species access in the aquatic system through anthropogenic activity has harmed the ecosystem and human health. In solving this problem, the use and development of inorganic material low-cost based as an effective adsorbent by good physico-chemical stability are one of this research's faces. The activated natural zeolite-magnetic composite (ANZ–Fe3O4) adsorbent material was prepared by using the co-precipitated method. Several adsorptions recognize the performance of removing Cr(VI) from a water sample; parameters such as pH, contact time, adsorbent mass, and temperature were studied. The result shows that the optimum adsorption occurs in pH 2, with a mass of adsorbent are 0.20 g, for 50 min of contact time at a temperature of 298 K. The adsorption mechanism was studied by using a linear and non-linear pseudo-first order (PFO) model, four pseudo-second order (PSO) models, Elovich model, and intraparticle diffusion model. The Langmuir, Freundlich, Dubinin-Radushkevich (DKR), Temkin, Brunauer-Emmett-Teller (BET), Redlich-Peterson, Harkin-Jura and Javonovic models were use to study the isotherm adsorption. Cr(VI) adsorption on ANZ-Fe3O4 followed with pseudo-second-order model (PSO) with R2 is 0.993. The comparative of linear PSO and non-linear PSO kinetic were wholly studied. The result shows that non-linear PSO model is the best-fit expression of mechanism adsorption of Cr(VI) on ANZ-Fe3O4 than the linear PSO model. The adsorption of Cr(VI) on ANZ-Fe3O4 in line with the Langmuir model with Qmax reaches 2.850 mg/g. The thermodynamics study shows that the adsorption process occurs exothermically and follows the physisorption process.